Piezocatalysis-combined advanced oxidation processes for organic pollutant degradation in water system - Heejin Yang; Chang-Gu Lee; Jechan Lee (Ultrasonics Sonochemistry)
The piezoelectric catalyst process has emerged as a promising technology for energy harvesting, effectively converting natural mechanical energies, such as wind, water flow, and waves, into usable electrical energy using piezoelectric materials. In recent years, there has been a growing interest in applying this technology to water treatment to address environmental challenges. Concurrently, research efforts have focused on enhancing the efficiency of piezoelectric catalysis by integrating it with advanced oxidation processes (AOPs). This combination has demonstrated significantly better performance than traditional single-process methods. This review offers a comprehensive overview of the fundamental principles of piezocatalysis and explores the evolution of research in this field. It provides a detailed analysis of how piezocatalysis has been developed and applied, particularly in water treatment. The review also includes a comparative assessment of various processes used to remove organic pollutants from water, focusing on recent advancements that combine piezocatalysis with AOPs. Furthermore, the limitations of the current research were discussed, and future research directions were suggested based on the overall findings. By summarizing the progress and challenges in this area, the review aims to provide valuable insights and guide future studies to enhance the effectiveness and application of piezoelectric catalysis in environmental remediation.